PENGEMBANGAN MULTIMEDIA TERHADAP PENGAJARAN PENDIDIKAN AGAMA KRISTEN PADA MASA PANDEMI COVID-19 - Santi Mali (Inculco Journal of Christian Education, 2021)
AbstractThis article aims to produce multimedia learning for Christian religious education in the midst of the COVID-19 pandemic, which is suitable for use as a learning resource. Aritkel for the development of multimedia Christian religious learning is viewed from the aspect of the ease of operation of the product, the aspect of the ease of the product to learn its contents, and the aspect of attractiveness. The average field trial results show that the multimedia learning of Christianity in terms of the ease of operation of the product, the aspect of the ease with which the product can be studied, and the aspect of attractiveness of the display is considered "very good". The results of this assessment indicate that the multimedia learning of Christianity with material of moral values and faith is suitable for use as a learning medium and learning resource.  AbstrakArtikel ini bertujuan untuk menghasilkan multimedia pembelajaran pendidikan agama Kristen ditengah pandemic COVID-19, yang layak digunakan sebagai sumber belajar. Aritkel pengembangan multimedia pembelajaran agama Kristen ditinjau dari aspek kemudahan produk untuk dioperasikan, aspek kemudahan produk untuk dipelajari isinya, dan aspek kemenarikan. Rata-rata hasil ujicoba lapangan menunjukkan bahwa multimedia pembelajaran Agama Kristen ditinjau dari aspek kemudahan produk untuk dioperasikan, aspek kemudahan produk untuk dipelajari isinya, dan aspek kemenarikan tampilan dinilai “sangat baik”. Hasil penilaian tersebut menunjukkan bahwa multimedia pembelajaran Agama Kristen dengan materi nilai-nilai moral dan keimanan yang dihasilkan layak digunakan sebagai media pembelajaran maupun sumber belajar.Sehingga multimedia layak